THE ESSENTIALS OF LOOKS: BEAUTY STANDARD IN LOCAL BRAND SKINCARE ADVERTISEMENT - Khotimah, Kusnul; Qothrunnada, Najla; Nur Lutfiana, Siti Fera; Suryaputra, Achmad Nabil (STBA Prayoga Padang, 2024)
This research discusses the beauty standards promoted by local Indonesian skincare brands,such as Wardah, Emina, and Kahf, in their advertisements. Beauty standards are ofteninfluenced by culture and media, reflecting social preferences for attributes such as fairskin and a natural look. Through a qualitative approach, this study analyzes the visual andtextual elements of advertisements to explore how these brands adapt their marketingstrategies to the needs of the domestic market. The results show that local brands not onlyreflect Indonesian cultural values but also begin to challenge the dominance of Westernbeauty standards. Their advertisements highlight a natural and healthy look, and offerproducts that are multifunctional and inclusive of various skin tones. In addition, theypromote halal and safe formulations, which are relevant to local consumer preferences. Thefindings illustrate the important role of local brands in shaping a more inclusive perceptionof beauty, while strengthening consumer loyalty to domestic products. This studycontributes to the literature on beauty, media, and consumer behaviour, with a focus on theIndonesian context.